Serum vitamin D levels and risk of prevalent tuberculosis, incident tuberculosis and tuberculin skin test conversion among prisoners - Maceda, Elisangela B. (Sci Rep, 2018)
Poor vitamin D status has been associated with tuberculosis (TB); whether poor status is cause or consequence of disease is uncertain. We conducted a case-control study and two nested case-control studies to determine whether vitamin D levels were associated with active TB, tuberculin skin test (TST) conversion, and risk of progression to the active TB in prisoners in Brazil. In multivariable conditional logistic regression, subnormal vitamin D levels (OR, 3.77; 95% CI, 1.04–13.64) were more likely in prisoners with active TB. In contrast, vitamin D was not found to be a risk factor for either TST conversion (OR, 2.49; 95% CI, 0.64–9.66) or progression to active disease (OR, 0.59; 95% CI, 0.13–2.62). Black race (OR, 11.52; 95% CI, 2.01–63.36), less than 4 years of schooling (OR, 2.70; 95% CI, 0.90–8.16), cigarette smoking (OR, 0.23; 95% CI, 0.06–0.79) were identified as risk factors for TST conversion. Risk of progression to active TB was found to be associated with cigarette smoking (OR, 7.42; 95% CI, 1.23–44.70). Our findings in the prison population show that poor vitamin D status is more common in individuals with active TB, but is not a risk factor for acquisition of latent TB or progression to active TB.